2004
DOI: 10.1099/vir.0.80402-0
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the oligosaccharides of the porcine reproductive and respiratory syndrome virus glycoproteins GP2a and GP5 for infectious virus production

Abstract: The arterivirus porcine reproductive and respiratory syndrome virus (PRRSV) contains four glycoproteins, GP 2a , GP 3 , GP 4 and GP 5 , the functions of which are still largely unresolved. In this study, the significance of the N-glycosylation of the GP 2a and GP 5 proteins of PRRSV strain LV was investigated. Both glycoproteins contain two predicted N-glycosylation sites that are highly conserved between North American-type and European-type PRRSV. Using site-directed mutagenesis, single and double mutant ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 37 publications
(37 reference statements)
2
62
1
1
Order By: Relevance
“…Two previous studies showed that the ablation of N-linked glycan in GP5 decreased the production of virus particles and infectivity of mutant viruses (2,47). However, these investigations did not examine whether the loss of glycosylation per se or other accidental structural alteration of GP5 or ORF5a protein due to artificially introduced amino acid substitutions accounted for the observed defective phenotypes.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Two previous studies showed that the ablation of N-linked glycan in GP5 decreased the production of virus particles and infectivity of mutant viruses (2,47). However, these investigations did not examine whether the loss of glycosylation per se or other accidental structural alteration of GP5 or ORF5a protein due to artificially introduced amino acid substitutions accounted for the observed defective phenotypes.…”
Section: Resultsmentioning
confidence: 67%
“…Some viruses lost specific glycosylation sites but propagated well in MARC-145 cells or PAMs (17), which implied that the existence of GP5-associated glycans per se was not vital to the life cycle of the virus. More importantly, an accidental amino acid mutation in the small ORF5a protein might also lead to the growth-defective phenotype of the mutants that showed loss of the glycans in GP5 by replacement of the N-encoding codon of ORF5 overlapping with ORF5a (2,47). In this study, we addressed this issue by introducing specific residues that existed in field PRRSV isolates with a glycan loss to the corresponding position in GP5 of the infectious cDNA clone pAJXM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORF1a and ORF1b encode the non-structural proteins, including three proteases and the RNA-dependent RNA polymerase (Snijder & Meulenberg, 1998); ORFs 2-5 encode glycosylated membrane proteins (GP2-GP5) and a small nonglycosylated protein E, ORF6 encodes a non-glycosylated membrane protein (M), and ORF7 encodes the nucleocapsid (N) protein that packages the viral RNA (Dea et al, 2000;Meulenberg et al, 1995). The major components of the envelope are GP5 and M, which form disulfide-linked heterodimers and are essential for particle assembly (Dea et al, 2000;Meulenberg et al, 1995;Wissink et al, 2005), while the minor proteins may play a role in defining tissue tropism (Wissink et al, 2004). All envelope proteins are required for infectivity (Wissink et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The role of cysteine 90 of the North American PRRSV N protein still remains to be determined. Using an European PRRSV isolate, Wissink et al (2004) have described a heterotrimeric complex of GP2, GP3 and GP4 and, without evidence, speculated a possible incorporation of E protein with this trimeric complex. Wieringa et al (2004) have recently shown a covalent association of the E protein with the GP2b-GP3-GP4 heterotrimers in EAV, suggesting a possible role of the heteromultimeric complex in the virus entry process.…”
mentioning
confidence: 99%